Hepatitis C and pregnancy - Floreani, Annarosa (Baishideng Publishing Group Co., Limited, 2013)
Acute hepatitis C is a rare event in pregnancy. The most common scenario is chronic hepatitis C virus (HCV) infection in pregnancy. During pregnancy in women with chronic HCV infection a significant reduction in mean alanine aminotransferase levels has been reported, with a rebound during the postpartum period. In few cases exacerbation of chronic hepatitis C has been reported in pregnancy. A cofactor that might play a role in the reduction of liver damage is the release of endogenous interferon from the placenta. Observations regarding serum HCV-RNA concentration have been variable. In some women HCV-RNA levels rise toward the end of pregnancy. In general, pregnancy does not have a negative effect on HCV infection. Conversely, chronic hepatitis does not appear to have an adverse effect on the course of pregnancy, or the birth weight of the newborn infant. The role of spontaneous abortion is approximately the same as in the general population. The overall rate of mother-to-child transmission for HCV is 3%-5% if the mother is known to be anti-HCV positive. Co-infection with human immunodeficiency virus (HIV) increases the rate of mother-to-child transmission up to 19.4%. Numerous risk factors for vertical transmission have been studied. In general, high viral load defined as at least 2.5 × 10(6) viral RNA copies/mL, HIV co-infection, and invasive procedures are the most important factors. Both interferon and ribavirin are contraindicated during pregnancy. Viral clearance prior to pregnancy increases the likelihood that a woman remains non-viremic in pregnancy with a consequent reduced risk of vertical transmission.